Bologna Through Ontario Eyes: The Case of the Advanced Diploma in Architectural Technology - Mitchell, Amy D.; Feltham, Mark; Trotter, Lane (Canadian Journal of Higher Education, 2015)
Inspired by Ontario’s burgeoning interest in postsecondary student mobility, this article examines how elements of Europe’s Bologna Process can help bridge the college–university divide of Ontario’s postsecondary system. Via discourse analysis of relevant qualification frameworks and program standards, it argues that the current system disadvantages students by failing to recognize that the Ontario advanced (three-year) diploma in Architectural Technology is equivalent to a baccalaureate-level qualification in the international context. The article concludes by discussing the larger significance of these findings in terms of ongoing debates about the “changing places” (HESA, 2012) of degrees in the Canadian higher education system.